Indole Acetic Acid Gibberellic Acid and Siderophore Production by PGPR Isolates from Rhizospheric Soils of Catharanthus roseus - Lenin, G (International Journal of Pharmaceutical & Biological Archive, 2012)
Indole Acetic Acid Gibberellic Acid and Siderophore Production by PGPR Isolates from Rhizospheric Soils of Catharanthus roseus